1976
DOI: 10.1159/000467314
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic Trace Analysis of β-Propiolactone in Sterilized Serum Proteins

Abstract: A method for detecting traces of β-propiolactone, which was previously described by SCHMITZ-MASSE, has been modified and adapted to the analysis of protein solutions. Using this method, the rate of hydrolysis of β-propiolactone (β-Pl) was examined and β-Pl sterilized commercial products were analyzed for possible residual nonhydrolyzed β-Pl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It is thus likely that it will also be effective in inactivating retroviruses associated with AIDS, as well as those associated with T cell leukemia (HTLV-I) [21] and some cases of hairy cell leukemia PPL is a potential carcinogen unless hydrolyzed by plasma hydrolases to the metabolizable non-toxic derivative, P-hydroxypropionic acid [23]. It has been found that the half-life for this transformation is 2% min when PPL is introduced into normal pooled human plasma; thus it is not surprising that the most sensitive gas chromatographic methods have not revealed unhydrolyzed PPL in plasma derivatives exposed to this compound [24]. Furthermore, these derivatives have been found to be non-mutagenic in the Ames test, while the original unhydrolysed compound was strongly mutagenic [25, 261. Thus the frequently expressed fear that PPL-treated plasma derivatives may be carcinogenic appears to be groundless.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus likely that it will also be effective in inactivating retroviruses associated with AIDS, as well as those associated with T cell leukemia (HTLV-I) [21] and some cases of hairy cell leukemia PPL is a potential carcinogen unless hydrolyzed by plasma hydrolases to the metabolizable non-toxic derivative, P-hydroxypropionic acid [23]. It has been found that the half-life for this transformation is 2% min when PPL is introduced into normal pooled human plasma; thus it is not surprising that the most sensitive gas chromatographic methods have not revealed unhydrolyzed PPL in plasma derivatives exposed to this compound [24]. Furthermore, these derivatives have been found to be non-mutagenic in the Ames test, while the original unhydrolysed compound was strongly mutagenic [25, 261. Thus the frequently expressed fear that PPL-treated plasma derivatives may be carcinogenic appears to be groundless.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there are several analytical methods for the determination of BPL in vaccines, such as high performance liquid chromatography (HPLC) [18], [19] and gas chromatography (GC) [7], [9], [11], [20], [21]. However, due to weak ultraviolet (UV) absorption of BPL [9], it is not advocated to be determined by HPLC with UV-detector.…”
Section: Introductionmentioning
confidence: 99%
“…'-3 Several reports have discussed its chemical activit most notably its behavior as a possible carcinogen. Present analytical methods such as gas chromatography (GC) 6 or colorimetry7 permit the detection of BPL levels to about 1 ~pm. '~' Detection of BPL presents major difficulties.…”
Section: Introductionmentioning
confidence: 99%